2014
DOI: 10.15226/jdodt.2014.00107
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Patient Knowledge of and Obstetric Provider Advice on Oral Health

Abstract: Research suggests pregnant women and obstetric providers possess inadequate knowledge about dental care that leads to underutilization of perinatal dental serviceS.Objectives: To examine the relationship between obstetric providers (OP) giving oral health advice to pregnant women and pregnant women's self-reported oral health awareness and behaviors (e.g., visiting dentist).Methods: Surveys were completed by 237 pregnant or post partum patients and 31 OPs from 12 outpatient obstetric practices located througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…17 A study of pregnant or postpartum women found that only about 20% of women reported that their obstetric provider advised them to visit a dentist while pregnant and fewer than 50% were told the importance of good oral health. 18 Those who were encouraged to see a dentist were more likely to pay attention to their oral health during pregnancy, supporting the importance of the provider’s advice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 A study of pregnant or postpartum women found that only about 20% of women reported that their obstetric provider advised them to visit a dentist while pregnant and fewer than 50% were told the importance of good oral health. 18 Those who were encouraged to see a dentist were more likely to pay attention to their oral health during pregnancy, supporting the importance of the provider’s advice.…”
Section: Introductionmentioning
confidence: 99%
“…A recent small study of maternity care providers found that although most providers had knowledge about the mother‐to‐infant vertical transmission of caries‐causing bacteria, fewer than 50% referred their patients for dental care or conducted oral examinations . A study of pregnant or postpartum women found that
only about 20% of women reported that their maternity care provider advised them to visit a dentist while pregnant, and fewer than 50% were told the importance of good oral health . Those who were encouraged to see a dentist were more likely to pay attention to their oral health during pregnancy, supporting the importance of the provider's advice.…”
Section: Introductionmentioning
confidence: 99%
“…Remiantis 2013 m. Amerikoje atlikto tyrimo rezultatais, pacientai, kuriems akušeriai patarė apsilankyti pas odontologą ir informavo apie geros burnos sveikatos svarbą, buvo šešis kartus labiau linkę daugiau dėmesio skirti savo burnos sveikatai. Taip pat keturis kartus labiau tikėti-na, kad šie pacientai apsilankė ar planuoja apsilankyti pas odontologą [17]. Tačiau galima teigti, jog tiek Amerikoje, tiek Europoje bendradarbiavimas tarp sveikatos priežiūros specialistų yra nepakankamas [17,18].…”
Section: Rezultatų Aptarimasunclassified
“…Taip pat keturis kartus labiau tikėti-na, kad šie pacientai apsilankė ar planuoja apsilankyti pas odontologą [17]. Tačiau galima teigti, jog tiek Amerikoje, tiek Europoje bendradarbiavimas tarp sveikatos priežiūros specialistų yra nepakankamas [17,18]. 2015 m. Prancūzi-joje atlikto tyrimo rezultatai atskleidžia, kad tik 26,3 proc.…”
Section: Rezultatų Aptarimasunclassified
“…However, encouragement by an obstetric provider of healthy behaviors increases a pregnant woman's likeliness to actually do the healthy behavior [9][10][11][12][13]. Once a pregnant woman visits the dentist, it is imperative to be cognizant of the status of both patients-mother and fetus.…”
Section: Introductionmentioning
confidence: 99%